Using the Powtoon Application as A Learning Media in Elementary School - Eka Putri, Agil; Riri Susanti (Journal International Inspire Education Technology, 2022)
In the world of education, the role of learning media is very necessary for students. The development of the times demands that humans are more progressive, thus students are required to find information independently from the results of interactions with the learning environment. Learning media is used to streamline the distribution of messages as a result of which there is a safe learning place. In fact, the use of learning media is still very minimal. This type of research is research and development using also applying the 4D model. The use of this learning media can make it easier for students to understand in teaching and learning activities. Through the Powtoon application, teachers can make it easier to develop learning media for students. The Powtoon application is an online animated video device that is relatively simple to use and can be used by teachers as well as students in teaching and learning.